2021
DOI: 10.1021/acssuschemeng.1c00931
|View full text |Cite
|
Sign up to set email alerts
|

Bundle-Type Columnar Cu2O Photoabsorbers with Vertical Grain Boundaries Fabricated Using Instant Strike-Processed Metallic Seeds and Their Enhanced Photoelectrochemical Efficiency

Abstract: The design to control grain boundaries (GBs) causing recombination losses as planar defects in the absorbing layers is an essential strategy for the development of highly efficient photoelectrochemical (PEC) reaction systems. We propose a method to design a progressive bundle-type columnar structure as an alternative to single crystals with the least defects, where the GBs are parallel to the charge transport movement and the electric field direction. An instant strike bias (0.01 s and −1 V vs Ag/AgCl) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…One would expect that the films with a thickness of one grain would show better PEC properties than that whose thickness includes several grains as the interfaces between the grains can act as sites for charge carrier scattering and electron–hole pair recombination. 30,31 However, scattering and electron–hole pair recombination occur in the film with fewer interfaces, as evidenced by the PEC properties of our samples. Additionally, the crack area percentages for the EA-LPD and C-LPD samples (9% and 15.5%, respectively) suggest that more hematite covers the surface in the EA-LPD samples, which increases the light absorption efficiency.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…One would expect that the films with a thickness of one grain would show better PEC properties than that whose thickness includes several grains as the interfaces between the grains can act as sites for charge carrier scattering and electron–hole pair recombination. 30,31 However, scattering and electron–hole pair recombination occur in the film with fewer interfaces, as evidenced by the PEC properties of our samples. Additionally, the crack area percentages for the EA-LPD and C-LPD samples (9% and 15.5%, respectively) suggest that more hematite covers the surface in the EA-LPD samples, which increases the light absorption efficiency.…”
Section: Resultsmentioning
confidence: 61%
“…They found that increasing the grain size from ∼40 to ∼100 nm causes a ten-fold increase in photoconductivity. Choi et al 31 developed a bundle-type columnar Cu 2 O photocathode with fewer GBs than its conventional polycrystalline film via the electrochemical deposition technique. The former structure showed better PEC properties than the latter due to the suppression of charge carrier scattering and electron–hole recombination.…”
Section: Introductionmentioning
confidence: 99%